Study of silica gel as self-healing agent in ordinary portland cement (OPC) mortar exposed to extremely high temperatures - Lim, Syh Ho (2015)
The study was conducted to investigate the effect of silica gel on the behaviour of Ordinary Portland Cement (OPC) mortar as self-healing material after exposed to extremely high temperature. An attempt has been made to define whether the spherical silica gel can carry out the healing mechanisms after put into the furnace and burn under extremely high temperature (500˚C, 600˚C and 700˚C). Three same dosages of silica gel (1% by weight of OPC) in the mortar mix were applied. There were other three sets of mortar mix without silica gel that were prepared to act as control specimen. Mortar properties after 3 days, 28 days, and exposure to extremely high temperature were conducted to study the compressive strength and its porosity. In order to determine its mechanical properties, 45 cubes (50 mm) with silica gel and another 45 cubes (50 mm) without silica gel were cast. All cubes specimens were tested until failure in compression machine. Based on the experimental results, silica gel will start to be activated after reacted with water (for day 3), which had almost similar strength with control cubes. However, in elevated temperature exposure, the compressive strength of cubes with silica gel is not influenced by the silica gel contribution once the temperature was elevated beyond 500 ˚C. The expansion of silica gel was believed to lead to the crack occurrence and decreased the strength of mortar cube. The percentage of porosity for OPC mortar with silica gel are much higher than the control cubes, means that it is more permeable than those control cubes due to the expansion development of the silica gel as the crack observed on mortar’s surface was happened at the interfacial transition zone between silica gel and cement matrix. Conclusively, the results revealed that silica gel only give significant effect to the compressive strength at day 3 and at 500˚C heating temperature